2018
DOI: 10.3390/ijms19082219
|View full text |Cite
|
Sign up to set email alerts
|

Asteriscus graveolens Extract in Combination with Cisplatin/Etoposide/Doxorubicin Suppresses Lymphoma Cell Growth through Induction of Caspase-3 Dependent Apoptosis

Abstract: Chemotherapy drugs action against cancer is not selective, lead to adverse reactions and drug resistance. Combination therapies have proven more effective in defeating cancers. We hypothesize that plant extract/fraction contains many/several compounds and as such can target multiple pathways as cytotoxic agent and may also have chemo sensitizing activities. We designed a study in which, Asteriscus graveolens (Forssk.) Less (A. graveolens)-derived fraction that contains sesquiterpene lactone asteriscunolide iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Many studies have examined the potential for plant-derived biologically-active compounds to induce apoptosis in cancer cells, with very promising results being obtained by the combination of the extract with a synthetic anti-cancer drug [51][52][53][54][55]. One such commonly-used anti-cancer agent is doxorubicin which is commonly used in the treatment of a wide range of cancers, including, different types of carcinomas or hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the potential for plant-derived biologically-active compounds to induce apoptosis in cancer cells, with very promising results being obtained by the combination of the extract with a synthetic anti-cancer drug [51][52][53][54][55]. One such commonly-used anti-cancer agent is doxorubicin which is commonly used in the treatment of a wide range of cancers, including, different types of carcinomas or hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies have proven to be promising alternatives for cancer therapy. As previously described [44], plant extracts contain several beneficial compounds that can target multiple pathways in cancer cells and can be more selective, sparing the normal cells. In addition, such combinations will enable a reduction in the dose of chemotherapy drugs.…”
Section: Cytotoxic Effects Of N Alba Extracts On Normal and Tumor Cellsmentioning
confidence: 96%
“…[5,20] Previous studies reported anticancer activity of asteriscunolides in human cell lines [21] and mouse cell lines. [14,15] Other compounds that were identified in the current research that also derived from the humulene skeleton are: bisabolone, 6-hydroxybisabol-2-en-1-one, germacrene-D, humulene-epoxide-II and α-humulene ( Table 1). [10] The high abundance of humulene derivatives in A. graveolens plants makes this species potentially pharmaceutically appropriate.…”
Section: Volatile Composition Analyses Using Various Extraction Methodsmentioning
confidence: 87%
“…[1,6,13] A. graveolens methyl tert-butyl ether (MTBE) extraction was tested for anticancer activity and found to be selectively cytotoxic to tumor cell lines in mice, but not to non-cancerous cells. [14,15] The postulated mechanism is stimulation of reactive oxygen species (ROS) activity followed by induction of apoptosis. [14,15] The plethora of therapeutic and antimicrobial activities of A. graveolens make it a promising plant candidate for further pharmacological and agricultural inquiries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation